Toward developing a model of stakeholder trust in waqf institutions - Hasan, Rashedul; Siraj, Siti Alawiah (Islamic Research and Training Institute, 2017)
Sustainability of Waqf institutions for poverty alleviation depends directly or indirectly on the donations received from the donors and the awareness of the society. This conceptual paper is an attempt to construct a model of stakeholder trust that could provide valuable insight on the issues that should be focused by the regulators, the mutawallis and the waqifs for ensuring a sustainability of waqf Institutions. The Modified Key Mediating Variable (MKMV) Model proposed in the paper includes a total number of eight variables. Commitment-trust theory is combined with Islamic Accountability and Stewardship theory toward shaping three conceptual models of trust into a much-needed unified model for exploring trust in the context of waqf institutions. Stakeholder trust is positioned as a mediator between independent (board benevolence, board ability, board integrity, board opportunism, communication and accountability) and the dependent variable (stakeholder commitment). Empirical results to support the model could not be provided due to the conceptual nature of the paper. The model can provide direction for reform towards sustainability of waqf institutions. The model is general enough that it can also be used for other conventional and non-profit religious organisations.